2017
DOI: 10.1017/s1751731116001634
|View full text |Cite
|
Sign up to set email alerts
|

Impact of amino acid and CP restriction from 20 to 140 kg BW on performance and dynamics in empty body protein and lipid deposition of entire male, castrated and female pigs

Abstract: Breeding leaner pigs during the last decades may have changed pig's empty body (EB) composition, a key trait for elaborating feeding recommendations. This research aimed to provide new experimental data on changes in the chemical composition of the EB of pigs from 20 to 140 kg BW. In addition, the impact of a reduction in the dietary CP associated with lower lysine, methionine + cystine, threonine and tryptophan levels was determined. In total, 48 males, castrates and females weighing 20 kg BW were allocated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 25 publications
7
52
1
Order By: Relevance
“…No dietary effect on ADG between LP and SP groups was observed, in accordance with previous studies in Alentejano (Iberian) pigs [31] and in heavy pigs [32][33][34][35]. In contrast, other authors found that feeding pigs ad libitum with protein-or lysine-deficient but adequate-energy diets during the finishing phase reduces ADG rate [36][37][38]. Differences between the abovementioned studies could be explained by the different growth rates of the pig breed [6], the pig body weight when the protein restriction is carried out [38], and the deficiencies in protein and essential amino-acid levels [31].…”
Section: Pig Performance and Carcass Quality Traitssupporting
confidence: 89%
“…No dietary effect on ADG between LP and SP groups was observed, in accordance with previous studies in Alentejano (Iberian) pigs [31] and in heavy pigs [32][33][34][35]. In contrast, other authors found that feeding pigs ad libitum with protein-or lysine-deficient but adequate-energy diets during the finishing phase reduces ADG rate [36][37][38]. Differences between the abovementioned studies could be explained by the different growth rates of the pig breed [6], the pig body weight when the protein restriction is carried out [38], and the deficiencies in protein and essential amino-acid levels [31].…”
Section: Pig Performance and Carcass Quality Traitssupporting
confidence: 89%
“…Animals, experimental diets and design A detailed description of the experimental design, diets and management protocol was previously presented by Ruiz-Ascacibar et al (2017). In brief, a total of 190 Swiss Large White pigs (66 FE, 66 EM and 58 CA) were used which originated from four farrowing rounds from the Agroscope sow herd.…”
Section: Methodsmentioning
confidence: 99%
“…In both treatments, the grower, finisher I and II diets for EM contained 5% more digestible CP, digestible lysine, methionine + cystine, threonine and tryptophan than the diets for FE and CA. The diet formulation, as well as, the analyzed contents of crude fat, crude fibre, ADF, NDF, CP and amino acids are outlined by Ruiz-Ascacibar et al (2017). Diets were produced at the Agroscope experimental feed mill and were pelleted (60°C, 4 mm diameter).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations